Studies on Technological Problems Associated with the Processing of Cooked Frozen Prawns 1. Storage Conditions of Raw Material in Relation to Quality - IYER, T. S GOPALAKRISHNA; CHOUDHURI, D. R.; PILLAI, V. K. (Fishery Technology, 2025)
The chemical and organoleptic properties of prawn held in ice for different days prior to cooking and the changes after freezing and. subsequent storage were studied with three different species of prawn viz. Metapenaeus monoceros, Metapenaeus dobsoni and Parapeneopsis stylifera. The optimum period for which the prawn can be kept under ideal conditions of icing prior to cooking has been worked out.